Petroleum biomarkers as tracers of low-level chronic oil contamination of coastal environments: A systematic approach in a subtropical mangrove. (June 2019) - Garcia, Marina Reback; Cattani, André Pereira; da Cunha Lana, Paulo; Figueira, Rubens César Lopes; Martins, César C.
Abstract: Petroleum biomarkers (hopanes, terpanes and steranes) are frequently assessed in estuarine sediments as tracers of oil input. In order to compare distinct patterns of hydrocarbon accumulation in mudflats, salt marsh and mangrove, sediments from two transects (control and impacted areas) were sampled in Paranaguá Bay, SW Atlantic. Concentrations of n -alkanes, polycyclic aromatic hydrocarbons (PAHs) and petroleum biomarkers (hopanes, terpanes and steranes) were determined, as well as bulk parameters (TOC, grain size and δ 13 C). N -alkanes concentrations were similar between control and impacted sites (respectively, 3.03 ± 1.20 μg g −1 and 4.11 ± 3.02 μg g −1 ) and reflected a high biogenic input. Conversely, PAHs and petroleum biomarker concentrations were three to six times higher in impacted site than the control site (respectively, 60.4 ± 23.3 ng g −1 and 22.0 ± 25.0 ng g −1 for PAHs and 197.7 ± 51.8 ng g −1 and 40.2 ± 32. ng g −1 for hopanes). Despite these differences, concentrations were lower than those reported for highly impacted areas worldwide. Diagnostic ratios and hydrocarbon parameters (e.g. total PAHs and total petroleum biomarkers) helped to distinguish human impact in the ecological zones, suggesting different sources and/or levels of weathering, confirmed by ANOVA tests. TOC played a fundamental role to the concentration of hydrocarbons, showing similar distributions along the transects. Petroleum biomarkers could clearly indicate the preferential sites of deposition and assign different levels of anthropic contamination by hydrocarbons, thus providing clear information about the chronic petroleum pollution in coastal sediments. Graphical abstract: Image 1 Highlights: Hydrocarbons assessed in mudflat, salt marsh and mangrove of a subtropical estuary. Hydrocarbon levels varied in correlation to organic carbon and fine sediments. PAHs and petroleum biomarkers in the impacted site were higher (3–6 fold). N -alkanes reflected biogenic hydrocarbon input in control and impacted sites. Petroleum biomarkers evidenced HCs contamination under a high biogenic background. Abstract : Petroleum hydrocarbons are reliable molecular markers to assess low-level hydrocarbon contamination in salt marshes and mangroves, along the terrestrial-aquatic gradient.